Tinjauan Yuridis terhadap Putusan Kasasi Mahkamah Agung Nomor 161 K/PDT.SUS-HKI/2023 Mengenai Sengketa Merek Dagang antara PS GLOW dan MS GLOW - Bagas Kristian Joenata; Rika Ratna Permata; Rai Mantili (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Trademarks have a very important function, namely as a differentiator from goods or services from other trademarks as well as a reputation for the goods or services being traded. Trademarks must be protected to prevent infringement in the form of unfair competition. The aim of this research is to understand the implementation of regulations and criteria regarding violations of brand similarity in essence as well as the use of marks that are not in accordance with those registered under brand law in Indonesia. The research method used in this research is a normative juridical approach, namely by using library materials in the form of positive law as the main material and then examining its implementation into practice. The primary legal material used by the author is Law Number 20 of 2016 concerning Marks and Geographical Indications, Law Number 15 of 2001 concerning Marks, Commercial Court Decision at the Surabaya District Court Number 2/Pdt.Sus-HKI/Merek/2022/ PN.Niaga.Sby, and Supreme Court Decision Number 161 K/Pdt.Sus-HKI/2023 as well as secondary legal materials, namely related literature, to analyze the decision.